2020
DOI: 10.3390/polym12020415
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Salts: An Efficient Curing Catalyst for Benzoxazine Based Coatings

Abstract: The effect of three different cerium salts (Ce(NO 3 ) 3 ·6H 2 O, CeCl 3 ·7H 2 O and Ce(OOCCH 3 ) 3 ·5H 2 O) on the ring-opening polymerization (ROP) of a model diamine-based benzoxazine (4EP-pPDA) was investigated. With the incorporation of the cerium salts, the curing temperature of 4EP-pPDA is reduced substantially, and the glass transition temperatures of the resulting networks are increased significantly. The three cerium salts exhibit different catalytic activities, which were analyzed by FT-IR, NMR, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The lowering of polymerization temperature was mediated by addition of Lewis acid catalysts, [ 255 , 269 , 271 , 306 , 307 ] metal salts [ 52 , 259 , 308 , 309 ], metal organic frameworks [ 310 , 311 ], and nanoparticles [ 13 , 303 , 312 , 313 ], which catalyze ROP either due to the presence of empty orbitals or metal ions which have interactions with the lone pair of heteroatoms in oxazine ring and mediate ROP.…”
Section: Acceleration Of the Rate Of Polymerization Via Intermolecular Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowering of polymerization temperature was mediated by addition of Lewis acid catalysts, [ 255 , 269 , 271 , 306 , 307 ] metal salts [ 52 , 259 , 308 , 309 ], metal organic frameworks [ 310 , 311 ], and nanoparticles [ 13 , 303 , 312 , 313 ], which catalyze ROP either due to the presence of empty orbitals or metal ions which have interactions with the lone pair of heteroatoms in oxazine ring and mediate ROP.…”
Section: Acceleration Of the Rate Of Polymerization Via Intermolecular Interactionmentioning
confidence: 99%
“…ZnCl 2 is a more effective catalyst than AlCl 3 and PCl 5 for the polymerization, as the resultant polybenzoxazine obtained has a much higher char yield (by 19%) than typical phenolic Mannich type polybenzoxazine with similar T g value [ 306 ]. Besides the nature of metal centers in catalysts, ease of dispersion of catalysts, such as cerium nitrate, in the monomer is another key factor which govern their catalytic efficiency [ 309 ]. Zinc stearate (10 mol%) was found to be the most effective catalyst to lower the T o of ROP of bio-based C-a monomer from 242 °C to 169 °C [ 311 ].…”
Section: Acceleration Of the Rate Of Polymerization Via Intermolecular Interactionmentioning
confidence: 99%
“…Among these approaches, the introduction of Lewis acid is the most convenient and versatile one. PCl 5 ( Zhang et al, 2021 ), PCl 3 , POCl 3 , TiCl 4 , and AlCl 3, and transition metal salts ( Sudo et al, 2010 ; Ran et al, 2012 ; Pei et al, 2021 ; Guorong et al, 2022 ) like CuCl 2 , AgCl, ZnCl 2 , NiCl 2 have been introduced into polybenzozine resins ( Zhang et al, 2019a ; Zhang et al, 2020 ). They can reduce the curing temperature to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of curing accelerators or catalysts has been investigated for oxazine-ring unsubstituted monomers ( i.e. 1,3-benzoxazine), such as m -phenylenediamine-formaldehyde oligomers, 24 salts such as cerium salts, 25 LiBr, and NaI, 26 organocatalysts such as methyl p -toluenesulfonate, 27 p -toluenesulfonic acid, 2-ethyl-4-methylimidazole, 26 or amines, 28,29 metal–organic frameworks, 30 etc . It has also been demonstrated that the catalyst type has an effect on the polymer structure.…”
Section: Introductionmentioning
confidence: 99%